Chronic endothelin receptor blockade reduces end-organ damage independently of blood pressure effects in salt-loaded heterozygous Ren-2 transgenic rats - Opocenský, M; Dvorák, P; Malý, J; Kramer, H J; Bäcker, A; Kopkan, L; Vernerová, Z; Tesar, V; Zima, T; Bader, M; Ganten, D; Janda, J; et al. (Physiological research, 2004)
The present study was performed to evaluate the role of an interaction between the endothelin (ET) and the renin-angiotensin systems (RAS) in the development and maintenance of hypertension and in hypertension-associated end-organ damage in heterozygous male and female transgenic rats harboring the mouse Ren-2 renin gene (TGR). Twenty-eight days old heterozygous TGR and age-matched transgene-negative normotensive Hannover Sprague-Dawley rats (HanSD) were randomly assigned to groups with normal-salt (NS) or high-salt (HS) intake. Nonselective ET(A)/ET(B) receptor blockade was achieved with bosentan (100 mg.kg(-1).day(-1)). All male and female HanSD as well as heterozygous TGR on NS exhibited 100 % survival rate until 180 days of age (end of experiment). HS diet in heterozygous TGR induced a transition from benign to malignant phase hypertension. The survival rates in male and in female heterozygous TGR on the HS diet were 46 % and 80 %, respectively, and were significantly improved by administration of bosentan to 76 % and 97 %, respectively. Treatment with bosentan did not influence either the course of hypertension (measured by plethysmography in conscious animals) or the final levels of blood pressure (measured by a direct method in anesthetized rats) in any of the experimental groups of HanSD or TGR. Administration of bosentan in heterozygous TGR fed the HS diet markedly reduced proteinuria, glomerulosclerosis and attenuated the development of cardiac hypertrophy compared with untreated TGR. Our data show that the ET receptor blockade markedly improves the survival rate and ameliorates end-organ damage in heterozygous TGR exposed to HS diet. These findings indicate that the interaction between the RAS and ET systems plays an important role in the development of hypertension-associated end-organ damage in TGR exposed to salt-loading.
Keywords: antagonisté endotelinového receptoru; multiorgánové selhání; receptory endotelinů; renin; Hypertension; geneticky modifikovaná zvířata; chlorid sodný; Female; sulfonamidy; krysa rodu Rattus; bosentan; Administration, Oral; zvířata; Bosentan; Endothelin Receptor Antagonists; Renin; Animals, Genetically Modified; potkani Sprague-Dawley; ženské pohlaví; krevní tlak; stupeň závažnosti nemoci; Male; hypertenze; Multiple Organ Failure; Severity of Illness Index; Rats; Receptors, Endothelin; Rats, Sprague-Dawley; Animals; aplikace orální; Sodium Chloride; míra přežití; Renin-Angiotensin System; mužské pohlaví; Blood Pressure; renin-angiotensin systém; Sulfonamides; Survival Rate